Upfront primary tumour resection and survival in synchronous metastatic colorectal cancer according to primary tumour location and RAS status: Pooled analysis of the Spanish Cooperative Group for the Treatment of Digestive Tumours (TTD). Issue 5 (May 2022) - Benavides, Manuel; Gómez-España, Auxiliadora; García-Alfonso, Pilar; González, Cristina García; Viéitez, Jose María; Rivera, Fernando; Safont, María José; Abad, Albert; Sastre, Javier; Valladares-Ayerbes, Manuel; Carrato, Alfredo; González-Flores, Encarnación; et al.
Abstract: Introduction: Retrospective studies and meta-analyses suggest that upfront primary tumour resection (UPTR) confers a survival benefit in patients with asymptomatic unresectable metastatic colorectal cancer (mCRC) undergoing chemotherapy, however a consensus of its role in routine clinical practice in the current era of targeted therapies is lacking. This retrospective study aimed to analyse the survival benefit of UPTR in terms of tumour location and mutational status, in patients with synchronous mCRC receiving chemotherapy and targeted therapy. Patients and methods: Survival was analysed in a pooled cohort of synchronous mCRC patients treated with a first-line anti-VEGF or anti-EGFR inhibitor in seven trials of the Spanish TTD group, according to UPTR, tumour-sidedness and mutational profiling. Results: Of 1334 eligible patients, 642 (48%) had undergone UPTR. UPTR was associated with significantly longer overall survival (OS; 25.0 vs 20.3 months; HR 1.30, 95%CI 1.15–1.48; p < 0.0001). UPTR was associated with significant OS benefit in both left-sided (HR 1.38, 95%CI 1.13–1.69; p = 0.002) and right-sided (HR 1.39, 95%CI 1.00–1.94; p = 0.049) tumours, RASwt (HR 1.29, 95%CI 1.05–1.60; p = 0.016) and BRAFwt (HR 1.49, 95%CI 1.21–1.84; p = 0.0002) tumours, and treatment with anti-EGFRs (HR 1.47, 95%CI 1.13–1.92; p = 0.004) and anti-VEGFs (HR 1.25, 95%CI 1.08–1.44; p = 0.003). Multivariate analysis identified number of metastatic sites, RAS status, primary tumour location and UPTR as independent prognostic factors for OS. Conclusion: Considering the selection bias inherent to this study, our results support UPTR before first-line anti-EGFR or anti-VEGF targeted therapy in right and left-sided asymptomatic unresectable synchronous mCRC patients. RAS/BRAF mutational status may also influence UPTR function. Highlights : Upfront primary tumor resection improves survival in right and left-sided mCRC Upfront primary tumor resection before targeted agents may improve survival Upfront primary tumor resection may benefit RAS/BRAF wild-type mCRC